Meningkatkan Keaktifan Dan Hasil Belajar Mahasiswa Melalui Metode Diskusi Kelompok Berbasis Pembelajaran Kooperatif Model Learning Together Pada Matakuliah Konsentrasi Pemasaran Di Fakultas Ekonomi Universitas Muhammadiyah Sumatera Utara - Dewi Andriany; Nel Arianty (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
This study aims to determine the extent to which students can be actively involved in the classroom by using group discussion methods based on cooperative learning model learning together, and also to know the extent to which students can express opinions and give responses to the opinions of his classmates communicatively by using the method of discussion group learning cooperative learning model together. The approach used is through classroom action research (Classroom Action Research), through cooperative learning methods. Steps taken with stages: (1) plan, (2) action, (3) observation, (4) reflection. The results showed that: (1) During the learning process using the method of group discussion based on cooperative learning method of learning together student learning activity can increase because students are empowered and given trust and actively involved in learning activities. The average percentage achievement of students' learning activity continues to increase which in pre cycle stage is only 34,1%, then reaching 65,8% percentage in cycle 1 and increasing again to 92% in cycle 2. (2) Positive impact from increasing activeness learning is on student learning outcomes which also experienced an increase wherein the precycle cycle the average value of students only 61.3 and increased in the cycle 1 to 75.7 and increased again to 83.09 on cycle 2.